Veríssimo, crítico do simbolismo (1899-1901) - Simões, Alvaro Santos [UNESP] (Instituto de Estudos Brasileiros, 2023)
From 1899 to 1901, José Veríssimo worked as the titular literary critic of the newspapers Jornal do Commercio e Correio da Manhã, both from Rio de Janeiro. By writing reviews about the literary releases of the turn of the century, Veríssimo had the opportunity to evaluate books of symbolist poetry published by disciples or admirers of Cruz e Sousa. The analysis of reviews of symbolist books intends to demonstrate briefly that the critic from Pará took these opportunities to evaluate directly or indirectly the work of the black poet.

De 1899 a 1901, José Veríssimo atuou como crítico literário titular dos periódicos Jornal do Commercio e Correio da Manhã, ambos do Rio de Janeiro. Escrevendo resenhas alentadas sobre os lançamentos literários da virada de século, Veríssimo teve oportunidade de apreciar livros de poesia simbolista publicados por discípulos ou admiradores de Cruz e Sousa. A análise de suas resenhas de livros simbolistas pretende demonstrar sumariamente que o crítico paraense aproveitava essas oportunidades para avaliar direta ou indiretamente a obra do poeta negro.
Veríssimo, critic of symbolism (1899-1901)
Keywords: José Veríssimo; Jornal do Commercio; symbolism; José Veríssimo; Jornal do Commercio; simbolismo